Bibliometric Analysis of Electric Vehicle Adoption and Market Trends - Judijanto, Loso; Hildawati, Hildawati (West Science Nature and Technology, 2025)
The adoption of electric vehicles (EVs) has emerged as a crucial solution to reduce carbon emissions and enhance sustainable transportation. This study conducts a bibliometric analysis to examine research trends, influential authors, and thematic developments in EV adoption and market trends. Using Scopus as the data source and VOSviewer for analysis, this study identifies key research clusters, including consumer behavior, charging infrastructure, environmental impact, and technological advancements. The findings reveal a significant increase in EV-related research, particularly in recent years, with the United States, China, and India leading contributions. Keyword analysis highlights critical themes such as government policies, battery technology, and vehicle-to-grid integration. Despite progress, challenges such as high upfront costs, limited charging infrastructure, and regional disparities persist. The study suggests future research directions focusing on battery sustainability, AI-driven mobility solutions, and smart grid integration. This bibliometric analysis provides valuable insights for researchers, policymakers, and industry stakeholders, contributing to the advancement of electric mobility research.